Self-Care and Self-Management Among Adolescent T2DM Patients: A Review - Eva, Jafrin Jahan; Kassab, Yaman Walid; Neoh, Chin Fen; Ming, Long Chiau; Wong, Yuet Yen; Abdul Hameed, Mohammed; Hong, Yet Hoi; Sarker, Md Moklesur Rahman (Frontiers in Endocrinology, 2018)
Uncontrolled hyperglycaemia can lead to macro- and microvascular complications. Adolescents with T2DM develop similar complications as in adults, including cardiovascular disease, stroke, myocardial infarction, renal insufficiency, and chronic renal failure. Although regular medical follow-up is essential to avoid long-term complications, patients with diabetes mellitus need to perform holistic self-care activities such as opting for a healthy diet, physical activity, self-monitoring, and proper medication. To the best of our knowledge, only a limited number of studies have focused on self-care activities and self-management, including self-care practices, supportive networks, and self-care education programs in adolescent with T2DM. Some of the studies focused on the appreciation of self-care in adolescents with T2DM. This review aimed to analyse self-care and self-management among adolescents with T2DM, and discuss the impact of self-care and self-management on glycaemic control. The difficulties faced by adolescents in self-managing their disease are also highlighted. Such information is essential for healthcare providers in promoting self-care practices among adolescents with T2DM. A thorough search of the literature was performed using three databases: Medline, Google Scholar, and Scopus. The articles focused on self-care and self-management of adolescents patients with T2DM aged between 12 and 19 years old were included. Findings from this review reveal that healthy food adaptation, adequate physical activity, proper medication practices, and regular glucose monitoring are the most common self-care practices. Parental involvement and clinician encouragement also contribute toward the practice of self-care and self-management among the adolescents with T2DM. In conclusion, independent self-management regimens and supportive networks for appropriate administration are vital factors to enhance clinical outcomes of adolescents with T2DM.